Atrial Fibrillation in Philadelphia Chromosome–negative Myeloproliferative Neoplasms: Thromboinflammatory Crosstalk with a Focus on the NLRP3 Inflammasome - Demska, Olga; Szandruk-Bender, Marta; Bruun, Niels Eske; Skov, Vibe; Kjær, Lasse; Larsen, Morten Kranker; Ellervik, Christina; Szmit, Sebastian; Hasselbalch, Hans Carl; Sobas, Marta (Thrombosis and Haemostasis, 2025)
The Philadelphia chromosome–negative myeloproliferative neoplasms (MPNs) and atrial fibrillation (AF) share a common proinflammatory and prothrombotic phenotype. Despite this overlap, patients with coexisting MPNs and AF remain undertreated and poorly characterized, with no specific antithrombotic guidelines addressing this dual pathology. Emerging evidence identifies the nucleotide-binding domain (NOD)-like receptor protein 3 (NLRP3) inflammasome as a central and common mediator of vascular diseases. This review explores the pathophysiologic convergence between MPNs and AF, with a focus on the NLRP3 inflammasome and its downstream cytokines (IL-1β, IL-18), as well as neutrophil extracellular traps (NETs), as unifying drivers of thrombosis, atrial remodeling, and clonal propagation. In MPNs, NLRP3 is activated by JAK2-driven inflammation and sterile danger signals, sustaining a cytokine milieu that promotes pyroptosis, fibrosis, and platelet–leukocyte–endothelial interactions. In AF, inflammasome overactivation in cardiomyocytes and fibroblasts contributes to ectopic activity, electrical remodeling, and fibrosis. NETs, which are enhanced by NLRP3, amplify thrombosis and may link the hematologic and cardiovascular components of the association between MPNs and AF. We critically evaluate the translational potential of inflammasome-derived biomarkers and identify NLRP3 inhibition as a promising adjunctive strategy in MPN patients with AF. The review calls for prospective studies to redefine antithrombotic management in this overlooked population, incorporating molecular, inflammatory, and arrhythmogenic risk dimensions.
Keywords: myeloproliferative neoplasms (MPNs); atrial fibrillation; JAK2V617F mutation thromboinflammation; NLRP3 inflammasome